Feasibility and safety of minimal‐incision thyroidectomy for Graves' disease: A prospective, single‐center study. Issue 9 (21st August 2012) - Perigli, Giuliano; Qirici, Etleva; Badii, Benedetta; Kokomani, Aurora; Staderini, Fabio; Luconi, Michaela; Crescioli, Clara; Mannelli, Massimo; Maggi, Mario; Cianchi, Fabio
Abstract Background The role of minimally invasive surgery in Graves' disease is still controversial. The aim of this study was to compare the clinical outcomes of patients undergoing minimal‐incision thyroidectomy with those undergoing conventional thyroidectomy for Graves' disease. Methods A prospective study was performed on 148 patients undergoing total thyroidectomy. Seventy‐one patients underwent minimal‐incision thyroidectomy and 77 underwent conventional thyroidectomy. Minimal‐incision thyroidectomy was proposed if the thyroid volume was ≤50 mL. Results There were no significant differences in the operative time between minimal‐incision thyroidectomy and conventional thyroidectomy. The length of skin incision was significantly shorter in the minimal‐incision thyroidectomy than that in the conventional thyroidectomy group. The incidence of postoperative complications was similar in the 2 groups. Patients undergoing minimal‐incision thyroidectomy experienced significantly less postoperative pain and were more satisfied with the cosmetic result than patients who underwent conventional thyroidectomy. Conclusions Minimal‐incision thyroidectomy is a feasible and safe option for the surgical treatment of selected patients with Graves' disease. © 2012 Wiley Periodicals, Inc. Head Neck, 2013